A 'match–no match' numerical and graphical kernel density approach to interpreting lead isotope signatures of ancient artefacts. (24th March 2020) - De Ceuster, Sarah; Degryse, Patrick
Abstract : A new method for interpreting lead isotope ratios of artefacts is presented: a numerical and graphical 'match–no match' with possible raw materials. By calculating the definite integral under the kernel density estimate plot of different mining districts, using open‐access software and legacy data, the relative probability that an object is made of an ore is indicated. A match with the reference data set may indicate the true origin, while no match indicates an unknown origin, that is, not present in the data set of mineral resources. Likewise, the composite or recycled nature of artefacts can be investigated in a probabilistic manner.